PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBASIS GAMIFIKASI TERHADAP HOTS SISWA KELAS IV SEKOLAH DASAR - Mamta Giri, Neha; Kumala Sari, Cut; Febri Rafli, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students Higher-Order Thinking Skills (HOTS) in mathematics require improvement, necessitating the use of innovative learning models. This study aimed to determine the effect of a gamification-based Problem-Based Learning (PBL) model on the HOTS of fourth-grade elementary school students, specifically in mathematics. A quantitative approach with a One-Group Pretest-Posttest design was employed, involving 21 fourth-grade students from SDN 2 Paya Bujok Tunong. Data were collected using HOTS-based tests and analyzed using the Shapiro-Wilk test and the Wilcoxon Signed-Rank Test. The results indicate that the implementation of the gamification-based PBL model had a significant effect on students' HOTS, with an Asymp. Sig. (2-tailed) value of 0.001. Thus, the gamification-based PBL model significantly influences fourth-grade students' HOTS in mathematics.